Relationship between Social Anxiety and Parental Authority among College of Education Students' at SQU - Hilal Z. Al- N abhani; Abdulhameed S. Hassan (Sultan Qaboos University, 2015)
The purpose of this study was to explore the relationship between parental authority and social anxiety. The study attempted to answer the following question: Are there significant differences in social anxiety due to parental authority factors: (support, control, psychological control, emotion and accomplishment of missions)? Data was collected from 172 students of College of Education at Sultan Qaboos University. The Parental Authority Questionnaire (FAQ), and Social Anxiety Scale (SAS) were used to assess variables. To answer the study question, re- gression analysis was used. Findings indicated that there was significant relationship between parental authority and social anxiety in several domains. The findings also revealed that there were significant differences in social anxiety due to mother authority and student's gender.